2018
DOI: 10.1155/2018/2128383
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation Study on Lateral Displacement of Pile Foundation and Construction Process under Stacking Loads

Abstract: Lateral displacement of pile foundation is crucial to the safety of an overall structure. In this study, a numerical simulation on the lateral displacement of pile foundation under stacking loads was conducted to determine its relation with different influencing factors. Simulation results demonstrated that stacking loads at the pile side mostly influence the lateral displacement of pile foundation. The lateral displacement of pile foundation increases by one order of magnitude when the stacking loads increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In the past, piles were unquestionably strengthened [4]. Nowadays, the designers are minimizing the length of reinforcing bars; therefore, they are scaling back the number of piles [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. This reduction needs excellent separation for the cases wherever the piles would entirely or partly require reinforcement, and in cases where the reinforcement has been eliminated.…”
Section: Basic Theory Of Reinforcement Concrete Pile On a Lateral Loadmentioning
confidence: 99%
“…In the past, piles were unquestionably strengthened [4]. Nowadays, the designers are minimizing the length of reinforcing bars; therefore, they are scaling back the number of piles [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. This reduction needs excellent separation for the cases wherever the piles would entirely or partly require reinforcement, and in cases where the reinforcement has been eliminated.…”
Section: Basic Theory Of Reinforcement Concrete Pile On a Lateral Loadmentioning
confidence: 99%
“…The formula was validated through analysis of a single pile case. Cai [12] employed numerical simulation to investigate the lateral displacement of pile foundations under surcharge loading, identifying variations in the impact of different factors. Ashour [13], after modifying and improving the conventional strain wedge method, eliminated the need for a constant multiplier.…”
Section: Introductionmentioning
confidence: 99%
“…More researches have been applied for the underground structures safety design in earthquake resistance since then. It was found that the dynamic response characteristics were quite different between the ground and underground structures of earthquake [8][9][10][11]. Jesmani et al and Angin indicated that earthquakes can damage tunnels especially in geohazard sites such as faults, changing strata, and ground fissures [12,13].…”
Section: Introductionmentioning
confidence: 99%